Single and Repeated Episodes of Candida Species Isolated From Cerebrospinal Fluid for Diagnosing Probable Candida meningitis - Xu, Lijun; Zhao, Handan; Zhou, Minghan; Lang, Guanjing; Lou, Haiyan (Frontiers in Microbiology, 2021)
Background: The clinical relevance of single or repeated episodes of Candida spp. in cerebrospinal fluid (CSF) in adult patients is debatable. Methods: Forty-two patients with positive Candida episodes in CSF were enrolled in this retrospective study. Results: A total of 42.9% (18/42) were determined to have probable Candida meningitis (PCM). Neurosurgery [odds ratio (OR) (95% confidence interval), OR: 14.4 (1.6–126.1), P = 0.004], lumbar drainage [OR: 5.8 (1.5–23.3), P = 0.009], VP shunt [(OR: 5.6 (1.2–25.8), P = 0.020)], external ventricular drainage [OR: 4.7 (1.3–17.7), P = 0.018], CRP ≥ 10.0 mg/L [OR: 4.9 (1.3–18.1), P = 0.034], and postsurgical broad-spectrum antibiotics [OR: 9.5 (1.8–50.5), P = 0.004] were risk factors associated with PCM. A single CSF Candida episode for the diagnosis of PCM had 7.7% (0.4–37.9%) sensitivity and 20.7% (8.7–40.3%) specificity, whereas repeated episodes of Candida had 66.7% (41.2–85.6%) sensitivity and 95.8% (76.9–99.8%) specificity. No significant difference was found in radiological imaging or CSF profiles between PCM and non-PCM patients. A total of 37.5% (9/24) of patients without PCM received empirical antifungal treatment, and 88.9% (16/18) of patients with PCM received preemptive antifungal treatment. PCM patients had hospitalized mortality rates of 50.0% (9/18). The odds ratio of mortality was 23.0 (2.5–208.6) for PCM patients compared with non-PCM patients (P = 0.001). Conclusion: Both single and repeated positive CSF samples have low validity for the diagnosis of PCM, suggesting that novel strategies for diagnosis algorithms of PCM are urgently needed. Empirical antifungal treatment should be started immediately for suspicious patients with risk factors.